Smarca4 deficiency induces Pttg1 oncogene upregulation and hyperproliferation of tubular and interstitial cells during kidney development - Xu, Jinshu; Zhou, Xianxiao; Zhang, Ting; Zhang, Bin; Xu, Pin-Xian (Frontiers in Cell and Developmental Biology, 2023)
Kidney formation and nephrogenesis are controlled by precise spatiotemporal gene expression programs, which are coordinately regulated by cell-cycle, cell type-specific transcription factors and epigenetic/chromatin regulators. However, the roles of epigenetic/chromatin regulators in kidney development and disease remain poorly understood. In this study, we investigated the impact of deleting the chromatin remodeling factor Smarca4 (Brg1), a human Wilms tumor-associated gene, in Wnt4-expressing cells. Smarca4 deficiency led to severe tubular defects and a shortened medulla. Through unbiased single-cell RNA sequencing analyses, we identified multiple types of Wnt4Cre-labeled interstitial cells, along with nephron-related cells. Smarca4 deficiency increased interstitial cells but markedly reduced tubular cells, resulting in cells with mixed identity and elevated expression of cell-cycle regulators and genes associated with extracellular matrix and epithelial-to-mesenchymal transition/fibrosis. We found that Smarca4 loss induced a significant upregulation of the oncogene Pttg1 and hyperproliferation of Wnt4Cre-labeled cells. These changes in the cellular state could hinder the cellular transition into characteristic tubular structures, eventually leading to fibrosis. In conclusion, our findings shed light on novel cell types and genes associated with Wnt4Cre-labeled cells and highlight the critical role of Smarca4 in regulating tubular cell differentiation and the expression of the cancer-causing gene Pttg1 in the kidney. These findings may provide valuable insights into potential therapeutic strategies for renal cell carcinoma resulting from SMARCA4 deficiency.